Industrial development in the different degrees of impact of the economic activities on the environment. - Amira, Khaoula; Alkama, Djamel (Journal of Human Sciences, 2021)
Industrial development in the different degrees of impact of the economic activities on the environment. Algeria has undergone major socio-economic changes that have affected its urban development and have affected ecological and environmental characteristics. Like Algerian cities, El Khroub experienced an unbridled development of its economic development which also resulted in a rapid and uncontrolled urbanization, at least at its beginning. A city with a primary agricultural vocation, external development al injunctions has reoriented it to form an economic pole of importance in the Constantinian crown. This article would be a demonstration of the impact of the zones of activity and industrial zones on the urbanization of the city by highlighting the consequences on the environment. It relies mainly on field data, survey, and statistics.